1989
DOI: 10.1159/000238652
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Imipenem into Human Pancreatic Juice following Single Intravenous Dose Administration<sup>1</sup>

Abstract: The penetration of imipenem into the human pancreatic juice following a single intravenous dose of 500 mg was investigated in five patients who had undergone pancreatic transplantation. With a special technique for segmental pancreatic transplantation it was possible to collect pure pancreatic juice at regular intervals. Simultaneous blood and pancreatic juice samples were collected immediately before drug administration and then at 0.5, 1, 1.5, 2.5, 3.5 and 5.5 h thereafter. The antibiotic concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Imipenem and ertapenem have both been shown to penetrate pancreatic tissue and pancreatic fluid at levels exceeding the minimum inhibitory concentration (MIC 90 ) for the most commonly seen bacteria after as little as a single intravenous dose. 105,106 Similar findings were documented for moxifloxacin, with concentrations greater than the MIC 90 after a dose of 400 mg, either oral or intravenous. 107 An in vitro study of the most commonly isolated bacteria from pancreatic necrosis -E. coli, Enterobacter cloacae, Enterococcus faecalis, Bacteroides fragilis -compared the effectiveness of imipenem, ertapenem and moxifloxacin against these pathogens.…”
Section: Diagnosis and Management Of Local Complications Of Acute Pansupporting
confidence: 65%
“…Imipenem and ertapenem have both been shown to penetrate pancreatic tissue and pancreatic fluid at levels exceeding the minimum inhibitory concentration (MIC 90 ) for the most commonly seen bacteria after as little as a single intravenous dose. 105,106 Similar findings were documented for moxifloxacin, with concentrations greater than the MIC 90 after a dose of 400 mg, either oral or intravenous. 107 An in vitro study of the most commonly isolated bacteria from pancreatic necrosis -E. coli, Enterobacter cloacae, Enterococcus faecalis, Bacteroides fragilis -compared the effectiveness of imipenem, ertapenem and moxifloxacin against these pathogens.…”
Section: Diagnosis and Management Of Local Complications Of Acute Pansupporting
confidence: 65%
“…In these conditions, while the serum drug levels are generally within normal ranges (4,8,25,28,32), the physiological interindividual variability is further enhanced by the disease. This is supported by the concentration of antibiotics in necrotic pancreatic tissue compared with nonnecrotic samples.…”
Section: Discussionmentioning
confidence: 99%
“…(26,46). Mezlocillin and imipenem belong to the same class of moderately liposoluble acids and therefore present the same characteristics of penetration into pancreatic juice (8,15,38), as rapid distribution and elimination (27); for this reason, the trough concentrations (at 6 h) may be lower than MICs for 90% of susceptible bacteria commonly found in pancreatic infections. How long the concentrations of antibiotic in the infection site remain above the MIC is a decisive factor for the therapeutic efficacy of beta-lactams (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients with these features received treatment with antibiotics. Other multicentric, double blind, randomized trial comparing meronem and placebo showed no statistically significant difference between the treatment groups for pancreatic or peripancreatic infection, mortality or requirement for surgical intervention, and did not support early prophylactic antimicrobial use in patients with severe acute necrotizing pancreatitis [37] (Table 5) [4,18,32,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%